Motor performance and correlates of mental health in children who are deaf or hard of hearing. (8th June 2015) - Fellinger, Matthäus J; Holzinger, Daniel; Aigner, Martin; Beitel, Christoph; Fellinger, Johannes
<x xml:space="preserve">Abstract</x> Aim This cross‐sectional study investigates the relationship between motor performance and mental health in a representative population of children with hearing impairment. Method Ninety‐three pupils (45 males, 48 females) aged 6 years to 16 years (mean 11y 3mo, SD 2y 9mo) with hearing impairment of at least 40dB and a Nonverbal IQ greater than 70 were assessed for motor performance with the Zürich Neuromotor Assessment (ZNA) and for mental health with the parent version of the Strengths and Difficulties Questionnaire (SDQ). Results Children with hearing impairment had lower motor performance scores in all four ZNA subscales compared with ZNA norms (z‐scores −1.42 to −2.67). After controlling for Nonverbal IQ, ZNA pure motor performance correlated negatively with the SDQ total difficulties score. Pure motor, pegboard, and dynamic balance subscales correlated negatively with peer‐relationship problems. Dynamic balance correlated negatively with emotional problems. Performance in pure motor and dynamic balance skills correlated negatively with age. Except for static balance, no correlation was found between motor performance and the degree of hearing impairment. Interpretation Results confirm that a high percentage of children with hearing impairment have poor motor performance. These problems are associated with difficulties in social relationships. Early recognition of these problems may lead to interventions to assist children with hearing impairment with their peer relationships.